ERGO: Breaking Down the Wall between Human Health and Environmental Testing of Endocrine Disrupters - Holbech, Henrik; Matthiessen, Peter; Hansen, Martin; Schüürmann, Gerrit; Knapen, Dries; Reuver, Marieke; Flamant, Frédéric; Sachs, Laurent; Kloas, Werner; Hilscherova, Klara; Leonard, Marc; Arning, Jürgen; et al. (International journal of molecular sciences, 2020)
ERGO (EndocRine Guideline Optimization) is the acronym of a European Union-funded research and innovation action, that aims to break down the wall between mammalian and non-mammalian vertebrate regulatory testing of endocrine disruptors (EDs), by identifying, developing and aligning thyroid-related biomarkers and endpoints (B/E) for the linkage of effects between vertebrate classes. To achieve this, an adverse outcome pathway (AOP) network covering various modes of thyroid hormone disruption (THD) in multiple vertebrate classes will be developed. The AOP development will be based on existing and new data from in vitro and in vivo experiments with fish, amphibians and mammals, using a battery of different THDs. This will provide the scientifically plausible and evidence-based foundation for the selection of B/E and assays in lower vertebrates, predictive of human health outcomes. These assays will be prioritized for validation at OECD (Organization for Economic Cooperation and Development) level. ERGO will re-think ED testing strategies from in silico methods to in vivo testing and develop, optimize and validate existing in vivo and early life-stage OECD guidelines, as well as new in vitro protocols for THD. This strategy will reduce requirements for animal testing by preventing duplication of testing in mammals and non-mammalian vertebrates and increase the screening capacity to enable more chemicals to be tested for ED properties.
Keywords: zdravotnické plány - realizace; průběh práce; Workflow; Environmental Monitoring; Health Impact Assessment; Humans; Risk Assessment; Data Warehousing; Endocrine System; cross-species extrapolation; Endocrine Disruptors; zvířata; hodnocení vlivů na zdraví; druhová specificita; adverse outcome pathway; thyroid hormone disruption; biomarkers; IATA; biotest; Biological Assay; Species Specificity; OECD; endokrinní systém; AOP; test guideline; biologické markery; endocrine disruption; integrated approach to testing and assessment; hodnocení rizik; Animals; lidé; skladování dat; Biomarkers; Health Plan Implementation; monitorování životního prostředí; endokrinní disruptory